Disharmonisasi Hukum Status Awak Kapal yang Tak Kunjung Reda: Antara Pekerja Migran dan Bukan Pekerja Migran - Aliqa Al-Syidriyah Dawani (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study examines the regulatory disharmony concerning the legal status of Indonesian seafarers working on foreign-flagged vessels and its legal implications for the protection of seafarers as migrant workers. Although Indonesia has ratified Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers (PPMI), the regulation does not explicitly accommodate seafarers within its protection scheme. The Constitutional Court Decision Number 127/PUU-XXI/2023 affirms that seafarers are categorized as migrant workers who are entitled to state protection. Nevertheless, there remains regulatory and institutional disharmony among the Ministry of Manpower, the Ministry of Transportation, and the Indonesian Migrant Workers Protection Agency (BP2MI), resulting in overlapping authorities, administrative barriers, and normative uncertainty. This research employs a normative juridical approach by examining relevant legislation and the Constitutional Court’s decision to identify the forms of disharmony and analyze their legal implications for the protection of seafarers working abroad. The findings indicate that seafarers constitute migrant workers subject to a lex specialis legal regime, thereby necessitating cross-sectoral policy harmonization and the establishment of an integrated and comprehensive legal framework to ensure legal certainty and optimal protection for Indonesian seafarers employed on foreign vessels.